Penerapan Teknologi dalam Dunia Makeup Inovasi dan Dampaknya terhadap Konsumen - Ifa Nurhayati; Anik Maghfiroh; Ainaya Alfatia; Niken Ayu Saputri Ananda; Zahrotul Firdaus; Nazla Rossa (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The beauty and makeup industry has undergone a remarkable transformation driven by rapid technological innovations. This study explores the integration of advanced technologies such as Artificial Intelligence (AI), Augmented Reality (AR), and Generative Adversarial Networks (GANs) within the makeup industry and how these tools influence consumer behavior, brand loyalty, and digital shopping experiences. Employing a qualitative descriptive method through literature review, the research highlights the impact of digital platforms, virtual try-on applications, and personalized product recommendations on consumer decision-making and satisfaction. Findings reveal that technology not only enhances consumer engagement and convenience but also fosters inclusivity and self-expression. However, challenges such as limited technology access, data privacy concerns, and counterfeit products persist. Addressing these issues is crucial to optimizing digital transformation in the beauty sector. This study contributes to the understanding of technological influence in modern consumer practices and offers strategic insights for industry stakeholders to develop more effective and ethical marketing approaches.